PENGARUH DUKUNGAN MANAJEMEN PUNCAK, KECANGGIHAN TEKNOLOGI INFORMASI, KUALITAS SISTEM INFORMASI AKUNTANSI DAN KINERJA INDIVIDUAL TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI: (Studi Kasus Pada Perusahaan Finance Di Kota Bengkulu) - Sari, Liza Puspa; Yulianasari, Nina; Mahrina, Helvoni (Jurnal Ilmu Akuntansi, 2022)
Th"is study aims to see how much influence top management support, information technology sophistication, information system quality and individual performance have on the effectiveness of accounting information systems in finance com"panies in Bengkulu city.From the results of the t-test above, obtained a significant value (p) f"or the variables of top management support, information technology sophistication, quality of accounting information systems and individual performance are all less than 0.05 (p < 0.05), so the hypothesis is signifi"cant. H1, H2, H3 and H4 are accepted meaning that partially, each independent variable (top man"agement support, information technology sophistication, accounting information system quality and individual performance) has a significant effect on the effectiveness of accounting information systems.Based on the results of the F-test research, a significant value (p) = 0.000 <0.05 is obtained, the model u"sed in this study is feasible and acceptable, and the fifth hypothesis (H5) is accepted, namely the"re is a significant influence between top management support, information technology sophistication, quality accounting information systems and individual performance on the effectiveness of accou"nting information systems in finance companies in Bengkulu City.